Thermal comfort conditions in traditional and sustainable, low - energy buildings. Issue 1 (1st August 2022) - Krawczyk, N; Kapjor, A
Abstract: Nowadays, each of us spends more and more time indoors. The article focuses on research on thermal comfort in a traditional and sustainable building. A sustainable building is equipped with heat pumps, a wind turbine, solar collectors and photovoltaic cells. It also has mechanical ventilation, which helps to minimize energy consumption and lower carbon dioxide emissions. The research was carried out using two methods, anonymous questionnaires and the Testo 400 microclimate meter. Based on the conducted research, the thermal sensations of the subjects and their preferences as to the prevailing conditions in the examined buildings were determined. The study also made it possible to compare the PMV index calculated using the Fanger model with TSV (obtained on the basis of anonymous questionnaires).